Treatment seeking behavior and related factors in patients with acute coronary syndrome - Tahere Taghizadeh-valdi; Seyedeh Noshaz T1, Mirhaghjou; Mohammad Taghi .N2*, Moghadamnia; Ehs , Kazemnezhad Leili (Guilan University of Medical Sciences, 2016)
Abstract Introduction: Acute Coronary syndrome is one of the most diagnosed and causes of death in the world, and treatment seeking behavior at the time of onset of symptoms and time spend on arriving to hospital is important for these patients, as it effects treatment and prognosis Objective: The aim of this study was to determine treatment seeking behavior and related factors in patients with acute coronary syndrome referring to Heshmat Educational-Therapeutic center in Rasht city. Methods: This descriptive analytical study was conducted on 370 patients with acute coronary syndrome, who were admitted to emergency, CCU and cardiac units chosen by sequential sampling method. The instrument was a 3-part questionnaire consisting of demographic and social information, disease information and questions to determine treatment seeking behaviors. Data were analyzed using descriptive analytical statistics such as Chi-square, Man-Whitney and logistic regression Results: The most common appropriate treatment seeking behaviors in the study population were rest (70%) and referring to heart related center (56.2%) and the most common inappropriate behaviors were not calling emergency medical services (85.9), not using sublingual TNG (68.6%) and delay for hours or days (60%). There was a significant correlation between the most common inappropriate behaviors and sex, place of living, complete insurance, education level, job status, monthly income level, comorbidity chronic disease, kind of disease, severity of pain, length of morbidity, and hospitalization for angina pain, first impression of chest pain, method of referring to medical center and first referred center Conclusion: In attention to inappropriate behaviors and transfer methods in majority of research samples in this study, educating high risk people is necessary